Getting things done - Malin, Virpi; Murphy, Jonathan; Siltaoja, Marjo (Dialogues in critical management studies, 2013)
This book explores the possibility of a progressive and transformative management which, while grounded in the analytic tradition and values of CMS, also confronts practical demands of meeting social needs. The format of the book is a discussion between and among CMS scholars with diverse viewpoints on CMS and critical engagement, and with different subject positions and domains of engagement. In the critical tradition, the book also gives voice to those who question a simple translation of theory into practice, as well as raising questions around the potential and limits to a progressively transformative management.